Chemical Compensation of Mitochondrial Phospholipid Depletion in Yeast and Animal Models of Parkinson's Disease. - Shaoxiao Wang; Siyuan Zhang; Chuan Xu; Addie Barron; Floyd Galiano; Dhaval Patel; Yong Joo Lee; Guy A Caldwell; Kim A Caldwell; Stephan N Witt (PLoS ONE, 2016)
We have been investigating the role that phosphatidylethanolamine (PE) and phosphatidylcholine (PC) content plays in modulating the solubility of the Parkinson's disease protein alpha-synuclein (α-syn) using Saccharomyces cerevisiae and Caenorhabditis elegans. One enzyme that synthesizes PE is the conserved enzyme phosphatidylserine decarboxylase (Psd1/yeast; PSD-1/worms), which is lodged in the inner mitochondrial membrane. We previously found that decreasing the level of PE due to knockdown of Psd1/psd-1 affects the homeostasis of α-syn in vivo. In S. cerevisiae, the co-occurrence of low PE and α-syn in psd1Δ cells triggers mitochondrial defects, stress in the endoplasmic reticulum, misprocessing of glycosylphosphatidylinositol-anchored proteins, and a 3-fold increase in the level of α-syn. The goal of this study was to identify drugs that rescue this phenotype. We screened the Prestwick library of 1121 Food and Drug Administration-approved drugs using psd1Δ + α-syn cells and identified cyclosporin A, meclofenoxate hydrochloride, and sulfaphenazole as putative protective compounds. The protective activity of these drugs was corroborated using C. elegans in which α-syn is expressed specifically in the dopaminergic neurons, with psd-1 depleted by RNAi. Worm populations were examined for dopaminergic neuron survival following psd-1 knockdown. Exposure to cyclosporine, meclofenoxate, and sulfaphenazole significantly enhanced survival at day 7 in α-syn-expressing worm populations whereby 50-55% of the populations displayed normal neurons, compared to only 10-15% of untreated animals. We also found that all three drugs rescued worms expressing α-syn in dopaminergic neurons that were deficient in the phospholipid cardiolipin following cardiolipin synthase (crls-1) depletion by RNAi. We discuss how these drugs might block α-syn pathology in dopaminergic neurons.